Health promotion activity in Kampung Biau,Bongawan - Patricia Sator; Che Ismail Che Noh; Izatul Natasya Abu Hanifah; Ephraim Koruthu Varugheese; Abdullah Bahiyudin Mohd Atan; Mahesan Rajalingam; Nurliayana Edayu Ahamad; Soon, Clarissa Syen Ling; Loo Yizhan; Day Ang Suhanna Sukar; Rozalinah Somponong; Bennielyn Benidict; et al. (Universiti Malaysia Sabah, 2016)
We from group 7 consist of 10 medical students and 5 nursing student had been sent to Kampung Biau, Bongawan to organize our Health Promotion event started from 24th of August until 2nd of September 2016. Coming along with us to observe our progress activity as a supervisor was Dr. Che Ismail Bin Che Noh, and our group is leads by Mr.Ephraim Koruthu Varugheese. Each member had their specific role in this group to maintain our activity progress smoothly throughout the program. Starting from the first day we arrived, the first activity that we have done is the opening ceremony for this Health Promotion that was held on the evening of the first day after we arrived. During our stay in the village, we also done several survey to get general overview about the region and health problems and then we can find some ways and took actions regarding these problems and to promote the health of the villagers. The various ways that we have done is such as: I. Rapid rural Appraisal (RRA) which includes the house-house visit, direct or field observation, key informant interview, individual interview, group meeting interview and discussion, health screening and also the social mapping. 2. Health education and health awareness by means of the exhibitions, talk, indoor and outdoor activities such as mini sports and tele match that have been participated by all the villagers from various age groups. 3. Visited to school in the area of Bongawan. This visit we aim to give a proper healthy lifestyle and talk to the student which will become the future generation to the country. For example, during our visit to the secondary school, we give a brief about the dangerous of smoking a conservative cigarette or e-cigarette. 4. Medical check-up. We held our medical check-up and health talk with the help from the local clinic in Bongawan. For example exhibition and talk for diabetes and breast cancer, the ways to prevent it. 5. Gotong-royong. We called all the villagers to joined cleaning Kg.Biau from garbage and avoid any breeding places for mosquito.